Heck, Suzuki and Sonogashira Cross-coupling Reactions using ppm level of SBA-16 supported Pd-complex - Sarkar, Shaheen M.; Lutfor, M. R.; M. M., Yusoff (Royal Society of Chemistry, 2015)
SBA-16 supported 1,2-diaminocyclohexane Pd-complex (100–500 mol ppm of Pd) was found to be an efficient catalyst in the palladium-catalyzed Mizoroki–Heck, Suzuki–Miyaura and copper-free Sonogashira cross-coupling reactions of aryl halides under mild reaction conditions. The Pd-complex efficiently promoted all of these coupling reactions with appropriate coupling partners to afford the corresponding coupling products with almost quantitative yield. The supported Pd-complex was readily recovered and used five times without a significant loss of its catalytic activity.